Comfort of A Co-Working Space in A Modern Café in Manado City - Wisnu Fauzan Ardiansyah; Sangkertadi Sangkertadi; Cynthia Erlita Virgin Wuisang (Interdisciplinary Social Studies, 2025)
This study investigates the comfort levels of co-working spaces within modern cafés in Manado City, focusing on three primary environmental factors: thermal, lighting, and acoustic conditions. The emergence of the Work from Café (WFC) trend among the younger workforce underscores the need for adaptive spatial environments that support productivity. Utilizing a mixed-method approach, both quantitative measurements and qualitative perceptions were collected from 34 café visitors actively working during weekdays. Tools such as the Delta Ohm HDTC 32.3, Lux Meter, and Sound Level Meter were employed to assess temperature, light, and noise levels, respectively. The results reveal that thermal comfort is the most influential factor, with air temperature showing a significant positive correlation with perceived comfort, whereas humidity and wind speed had minimal impact. Conversely, lighting intensity and glare were found to have weak correlations with visual comfort, and acoustic measurements indicated a discrepancy between objective noise levels and subjective perceptions, suggesting user adaptation. These findings highlight the divergence between physical measurements and individual experiences in informal workspaces. The study concludes that enhancing thermal conditions, managing acoustics, and re-evaluating lighting design are essential strategies for café operators aiming to optimize their spaces for co-working users. The research contributes to a deeper understanding of environmental comfort in semi-public work settings and offers practical insights for architectural and interior design improvements in modern cafés.